Dialogues and musical confluences in Antioquia. Four paradigms in traditional Andean strings (Encuentros, 2017)
The article, an outcome of research Andean string groups in Antioquia. Dialogue between popular and academic traditions, 1979-2012 (Colciencias, University of Antioquia), analyses the dynamics of traditional Andean strings in this region of Colombia through the life and work of four of its most prominent representatives, i.e. Luis Uribe Bueno, Jesús Zapata Builes, Elkin Pérez Álvarez, and León Cardona García. It shows how during the second half of the twentieth century these musicians contributed to position the imaginary of a national music based on the main Andean genres and transform them into expressions with high academic content regarding their use and function —like chamber music—,their appropriation and circulation, and in their compositional and interpretive proposal. From this perspective, these leaders set three bridges of dialogue between popular and academic traditions in Antioquia —one pedagogical, another aesthetic and a third one which leads tradition towards the musical industry—.
Keywords: Traditional Andean strings; string music in Antioquia; folk music traditions; academic traditions; Colombian Andean music; bandola-tiple-guitar; Colombia’s music industry.